Urinary biomarkers of nucleic acid oxidation and methylation in workers exposed to low concentrations of benzene. (1st October 2020) - Lovreglio, Piero; Stufano, Angela; Andreoli, Roberta; Tomasi, Cesare; Cagnazzi, Paola; Barbieri, Anna; Soleo, Leonardo; De Palma, Giuseppe
Highlights: Urinary biomarkers of nucleic acid oxidative damage are always higher at the end of shift. Exposure to low-levels of benzene is related to urinary end of shift 5-Methyl-Cytosine. Urinary 5-Methyl-Cytosine is a potential biomarker to evaluate nucleic acid methylation status. Abstract: The study aims to investigate the influence of exposure to low concentrations of benzene on urinary biomarkers of nucleic acid oxidative damage and methylation. Benzene exposure was characterized for 93 coke production workers by measuring both airborne benzene and S-phenylmercapturic acid (SPMA) and unmodified benzene (U-B) in urine samples, collected at the end of the shift (ES) and at the next morning before shift (next BS). In the same urinary samples, biomarkers of nucleic acid oxidative damage and methylation were determined. Urinary concentrations of cotinine and creatinine were also determined to evaluate the smoking effect and to normalize urinary concentrations of analytes, respectively. The biomarkers of benzene internal dose, of oxidative damage (8-hydroxyy-7, 8-dihydroguanine, 8-hydroxy-7, 8-dihydroguanosine and 8-hydroxy-7, 8−2'deoxyguanosine) and some of the biomarkers of nucleic acid methylation (5-Methyl-Cytosine, 1-Methyl-Guanine and 7-Methyl-Guanine) were higher in the ES than the next BS samples. Positive associations between ES 5-Methyl-Cytosine and both SPMA and U-B were found. In conclusion, occupational exposure to low levels of benzene seems to be related to urinary ES 5-Methyl-Cytosine that could be a possible biomarker to evaluate the changes of the nucleic acid methylation status.